GENDER COMMUNICATION STRATEGY IN INDONESIA - Muhammad Edy Susilo; Nurul Latifatun Nisa (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2018)
Reformation began in 1998, since then, the issue of women's quota in the legislature has surfaced. This issue was successfully established into a political policy that accommodates affirmative action for women in parliament. Quota policies that contain at least 30% of women's representation apply to the number of delegates, candidates, and officials. The purpose of this policy is to ensure the implementation of rules that pro to women. Nevertheless, still 30% quota has not been fully fulfilled. Some region in Indonesia show different development. This research was conducted in Minahasa, it has the largest number of women representatives of legislative members in Indonesia and in Wonosobo with the least number of women representatives in the legislature in Indonesia. This research uses experimental method and qualitative analysis. Experiments were conducted to find out how respondents rated female politicians and male politicians. The results of the experiment were further investigated with in-depth interviews and focus group discussions. Research shows that male respondents perceive male politics as more capable than female politicians. Meanwhile, female respondents also see male politicians more competent. This is in line with the stereotyping gender theory. Women politicians who have good political communication skills have the opportunity to be elected in political circles. The social structure also affects women's election as politicians. In Wonosobo, it is known that religious groups do not approve of women becoming legislators.